About one class families of space curves order three - Petruškevičiūtė, D. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. Петрушкявичюте. Об одном классе семейств пространственных кривых третьего порядка D. Petruškevičiūtė. Apie vieną trečios eilės erdvinių kreivių šeimų klasę